The Concept of Spiritual-Based Character Education At Nusantara Beriman Islamic Boarding School Poleang Kendari, Southeast Sulawesi - Defi Firmansyah; Muh. Karumiadri; Muh. Nur Rochim Maksum (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
Responding to the moral problems that are rife in Indonesia, the concept of character education is a solution in dealing with these problems. This is related to the increase in juvenile delinquency among Muslims who are increasingly living their lives away from the application of Islamic values. Related to it, Nusantara Beriman Islamic Boarding School is one of the Islamic boarding school educational institutions that focuses on educate the morals of his students by trying to optimize spiritual-based character education that is instilled through activities at Islamic boarding schools. In this research, the author will examine the concept of character education which focuses on spiritual activities at Nusantara Islamic Boarding School Poleang. The method used by researchers is a descriptive qualitative method by making the Nusantara Beriman Islamic Boarding School as the object of research. The results of this research are, the life student dynamics at Nusantara Beriman Islamic Boarding School which emphasizes to educate student character through spiritual activities like reciting the Qur'an on the sidelines of formal education, qiyamu al-layl activities every night and traveling preaching or safari da’wah, aiming to educate the students character who have noble morals by making worship (ubudiyah) as the basic for building character. With this concept, students will also get used to pay attention to ubudiyah aspects in the process of studying and not putting it aside, so that a human character is formed that is not only intelligent in science but will continue to prioritize morals in socializing